Wonderful and wild world of women's health. (24th January 2017) - Thorp, John
Abstract : Deputy Editor‐in‐Chief, Dr John Thorp, discusses his top articles from this issue in an audio podcast available at:https://soundcloud.com/bjog/february-editors-choice-2017 .